Content validation of the Brazilian version of the General Comfort Questionnaire - Geórgia Alcântara Alencar Melo; Renan Alves Silva; Letícia Lima Aguiar; Francisco Gilberto Fernandes Pereira; Nelson Miguel Galindo Neto; Joselany Áfio Caetano (Universidade Federal do Ceará, 2019)
Objective: to validate the content of the Brazilian version of the General Comfort Questionnaire. Methods: validation study; the instrument was evaluated by 22 judges for clarity, comprehension, relevance, association with comfort and classification of items in the domains. The agreement among judges was analyzed through a binomial test and the Content Validation Index. Results: of the 48 items, ten were distributed in the physical domain, with agreement between 0.5 and 1.0; 11 in the socio-cultural domain (0.59 - 0.90); ten in the environmental (0.68 - 1.0); and 17 items in the psycho-spiritual (0.45 - 1.0). Regarding the criteria of clarity and association with comfort, all items obtained satisfactory evaluation and four did not reach the recommended agreement. Conclusion: the instrument is valid for measuring this construct and verifying the quality of care produced by the nursing staff according to the judges' perception, since the overall Content Validity Index was 0.81.